Clinical Development Approaches and Statistical Methodologies to Prospectively Assess the Cardiovascular Risk of New Antidiabetic Therapies for Type 2 Diabetes. (January 2015) - Geiger, Mary Jane; Mehta, Cyrus; Turner, J. Rick; Arbet-Engels, Christophe; Hantel, Stefan; Hirshberg, Boaz; Koglin, Joerg; Mendzelevski, Boaz; Sager, Philip T.; Shapiro, Deborah; Stewart, Murray; Todaro, Thomas G.; et al.
In December 2008, the US Food and Drug Administration (FDA) issued a guidance for industry requiring sponsors to demonstrate that a new antidiabetic therapy being developed to treat type 2 diabetes does not increase cardiovascular (CV) risk to an unacceptable extent. CV events reported during phase 2 and phase 3 trials should be prospectively and independently adjudicated. Before submission of a new drug application or biologics license application, sponsors should compare the incidence of major CV events occurring with the investigational agent versus the control group to show that the upper bound of the 2-sided 95% confidence interval (CI) for the estimated risk ratio is less than 1.8. If the CI includes 1.3, a postmarketing trial will be necessary to definitively show that the upper bound of the 95% CI for the estimated risk ratio is then less than 1.3. In 2012, the European Medicines Agency (EMA) issued an updated guideline on the clinical investigation of medicinal products in the treatment or prevention of diabetes mellitus that detailed its CV safety assessment requirements. Although similar to the FDA guidance, the EMA guideline does not prospectively define any pre- or postapproval risk margins. This expert perspective, prepared by members of the Cardiac Safety Research Consortium, discusses clinical development strategies, operational issues, and statistical methodological issues to satisfy the FDA's CV safety requirements, and, where appropriate, the EMA guideline. Actual case examples, where applicable, are presented.